Pengalaman Pembelajaran Daring Pada Penggunaan Whatsapp Bagi Mahasiswa Uin-Su Di Era Pandemi Covid-19 - Nunzairina Nunzairina (Program Studi Pendidikan Biologi, 2022)
This study aims to determine the use of WhatsApp which is used by students of the State Islamic University of North Sumatra in conducting online learning, then to find out the obstacles of online learning to students of the State Islamic University of North Sumatra and to find out how to solve the obstacles of lectures via WhatsApp. This type of research is comparative research, namely comparison. The population in this study were all students of Communication Studies semester IV Stambuk 2019 totaling 179 students. The selection of research samples was determined by randomly selecting two classes or random sampling. This study uses a quantitative approach and uses an online survey in the form of a google form to collect the necessary data or information. The results show that the effect of online learning via WhatsApp is in a good category based on the average value of the percentage of learning via WhatsApp obtained with a percentage value (67.8 %). Then the results of the study of the sub-variable of the effect of using WhatsApp on affective behavior obtained an average score of 72.5%, namely in the statement